The Effectiveness of Deep Breathing Relaxation Techniques in Reducing Pain in Postoperative Patients - Putri, Maidina; Nurlela, Lela; Kirana, Sukma ayu Candra; Arnianti, Arnianti; M. Khalid Fredy Saputra (International Journal of Health Sciences, 2025)
Background: Postoperative pain is a common problem experienced by patients after surgery. Inadequate pain management can slow the recovery process, increase physiological stress, and reduce the patient's quality of life. One non-pharmacological method that can be used is deep breathing relaxation techniques, which aim to increase oxygenation, reduce muscle tension, and provide a calming effect. Objective: To determine the effectiveness of deep breathing relaxation techniques in reducing pain intensity in post-operative patients. Method: The study used a quasi-experimental design with a pre-test approach. post-test control group Design. The sample consisted of 60 elective post-surgery patients at Hospital X, divided into an intervention group (n=30, given deep breathing relaxation techniques) and a control group (n=30, given standard care). Pain intensity was measured using a Visual Analog Scale (VAS) before the intervention and 30 minutes after the intervention. Data analysis was performed using paired t- test and independent t- test. Results: The mean pain score before intervention in the deep breathing relaxation group was 5.8 (SD ±1.2), decreasing to 3.2 (SD ±1.1) after intervention. Meanwhile, in the control group, the pain score before intervention was 5.7 (SD ±1.3) and after 30 minutes it became 5.4 (SD ±1.2). Statistical tests showed a significant difference between the two groups (p < 0.05). Conclusion: Deep breathing relaxation techniques are effective in reducing pain intensity in postoperative patients. This method can be recommended as a simple, inexpensive, and easy-to-implement non-pharmacological therapy to support postoperative pain management.